Environmental impacts and embodied energy of construction methods and materials in low-income tropical housing - Hashemi, Arman; Cruickshank, Heather; Cheshmehzangi, Ali (MDPI, 2015)
This paper evaluates the current conditions of Ugandan low-income tropical housing with a focus on construction methods and materials in order to identify the key areas for improvement. Literature review, site visits and photographic surveys are carried out to collect relevant information on prevailing construction methods/materials and on their environmental impacts in rural areas. Low quality, high waste, and energy intensive production methods, as well as excessive soil extraction and deforestation, are identified as the main environmental damage of the current construction methods and materials. The embodied energy is highlighted as the key area which should be addressed to reduce the CO2 emissions of low-income tropical housing. The results indicate that the embodied energy of fired bricks in Uganda is up to 5.7 times more than general clay bricks. Concrete walling is identified as a much more environmentally friendly construction method compared to brick walling in East African countries. Improving fuel efficiency and moulding systems, increasing access to renewable energy sources, raising public awareness, educating local manufacturers and artisans, and gradual long-term introduction of innovative construction methods and materials which are adapted to local needs and conditions are some of the recommended actions to improve the current conditions.